Singing the Fronde: Placards, Street Songs, and Performed Politics. Issue 1 (2nd January 2019) - Romey, John
Abstract : The Fronde generated vast amounts of ephemeral printed media that circulated polemical information and shaped public discourse. Pamphlets, street songs, and placards, known as mazarinades, survive as artefacts of performances that jostled for attention in chaotic urban public spaces. In this article I analyse three placards produced during the Fronde to demonstrate their utilitarian function as a tool of mass communication that sometimes incorporated songs drawn from the repertoires of literary elites and street singers. When a placard was read à haute voix or an inscribed song was sung, these objects engendered performances that filled Paris's public spaces with political propaganda. Because songs printed on placards set new texts to pre-existing tunes, the layering of songs fostered webs of intertextual and intermusical references. By determining the significance of a particular tune to contemporary audiences, we can enrich textual and visual analyses and begin to determine how different social groups might have responded to the mazarinades . Through song, individuals participated in communal social acts that memorialized contemporary events and forged connections with events in living memory. Placards, then, illustrate how effective political messaging in early modern Paris in part translated to controlling the urban soundscape.